Athletic Department Practices Related to the Academic Performance and Persistence of Student-Athletes - Unruh, Richard L. (My University, 2001)
This research project applies student academic performance and persistence findings presented by A. Astin and V. Tinto to the practices of intercollegiate athletic departments and their relationships with faculty and student-athletes. Through survey research of 178 football and men's basketball players, athletic administration, coaches, and faculty in Division I athletic programs, including cross tabulation and frequency analysis of data, this study examined athletic department practices related to the academic performance and persistence of the student-athletes. Four parallel convenience samples were identified and surveyed during this study. The student-athlete sample (N=106) was stratified to include only football and men's basketball players who were of junior or senior status and had been enrolled at that institution for at least one year. The coach sample (n=29) included only football and men's basketball coaches. Three football and two basketball coaches (n=5) comprised each site sample. The administrative sample (n=25) included athletic directors and/or assistant or associate directors responsible for academic support and/or directors or coordinators of academic support programs. Administrators at each site (n=3) were selectively sampled. The faculty representative sample (n=8) included faculty who currently held the position of faculty athletic representative. Independent variables were organized into five categories: athletic department academic policies, practices, and interdepartmental relationships; athletic department relationships with academe; athletic-academic support services procedures, activities, and responsibilities; student-athlete preparation, development, involvement in campus life, and relationships with nonathlete peers; and coaches' actions, attitudes, and responsibilities. The findings of this study provided knowledge and understanding of how athletic department practices relate to the persistence and academic success of student-athletes. Recommendations included providing technology to students, creating freshmen interest groups across athletes, enhancing student-athlete development programming, and improving relationships with faculty on campus.
Keywords: models; relationship with campus; academic performance; persistence